Influence of differently directed motor activity on indicators of external respiratory functions in the process of special physical training in boxing - Neupokoev, S. N.; Bredikhina, Yu. P.; Shilko, V. G.; Guseva, N. L. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to analyze the influence of multidirectional muscle activity on the functional parameters of the external respiration apparatus during the performance of special physical training exercises in boxing.